2014
DOI: 10.1111/aji.12351
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Myeloid-derived Suppressor Cells in the Blood and Endometrium is Associated with Early Miscarriage

Abstract: The miscarriage patients harbor reduced level of functionally suppressive MDSC in blood and endometrium as compared to healthy control women with successful pregnancies. These results suggest MDSC regulate maternal tolerance in healthy pregnancies and that drug inducing MDSC could have therapeutic implication in the miscarriage patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 47 publications
4
67
0
3
Order By: Relevance
“…These results parallel data from others showing an enrichment of Tregs in human decidua and an association between diminished Treg accumulation and pregnancy failure (32,34,35). Recently, reduced MDSCs in peripheral blood of patients with early miscarriage and a depletion of MDSCs leading to pregnancy failure in mice have also been shown (36,37). Taken together, our results add new aspects of MDSC biology in human pregnancy as being crucial during physiological conditions, that is, in human pregnancy, and point again toward a role for GRMDSCs in protecting the fetus from immune rejection.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results parallel data from others showing an enrichment of Tregs in human decidua and an association between diminished Treg accumulation and pregnancy failure (32,34,35). Recently, reduced MDSCs in peripheral blood of patients with early miscarriage and a depletion of MDSCs leading to pregnancy failure in mice have also been shown (36,37). Taken together, our results add new aspects of MDSC biology in human pregnancy as being crucial during physiological conditions, that is, in human pregnancy, and point again toward a role for GRMDSCs in protecting the fetus from immune rejection.…”
Section: Discussionsupporting
confidence: 89%
“…Because CD66b staining cannot distinguish between immature GR-MDSCs with suppressive capacities and mature granulocytes, these results have to be viewed with caution. A recent study on MDSCs in early pregnancy using CD33 as a marker for MDSCs found a diffuse distribution of CD33 + cells in the endometrium (36). Similar to CD66b, CD33 is not specific for MDSCs but is also expressed on granulocytes and monocytes, so that to date no method exists to clearly identify the exact localization of MDSCs at the maternal-fetal interface.…”
Section: Discussionmentioning
confidence: 99%
“…In both mice and patients exacerbation of allergy-induced asthma is associated with diminished immune suppressive function of Gr-MDSC [110]. Recent studies also show a correlation between reduced levels of MDSC and miscarriage [111, 112], suggesting that MDSC may also be implicated in normal pregnancies. Therefore, MDSC may play a critical role in combating autoimmune and allergic reactions and have the potential to be exploited as therapeutic agents for multiple diseases involving harmful immune responses.…”
Section: Mdsc May Be Useful For Inducing Tolerance In Pathologicamentioning
confidence: 99%
“…MDSCs, however, did not follow control levels on day 2 of pregnancy. In this case, control mice showed a significant increase in MDSC levels (P < 0.0001) between days 0 and 2 of pregnancy), which could probably ensure the development of the required immunosuppressive state (Nair et al 2015, Zhao et al 2016, while l-Cn-treated mice failed to further increase these levels (P = 0.018, Figure 5 Effect of in vivo l-Cn treatment on ovarian histology. Superovulated female mice received daily injections of 2.5 mg l-Cn for 5 or 7 days, caged with males and ovaries were isolated 18 h post-hCG injection on day 0 of pregnancy.…”
Section: Maternal Systemic Immunity Upon L-cn Treatmentmentioning
confidence: 96%